2019
DOI: 10.1002/cam4.1983
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of ten‐eleven translocation 1 reverses gemcitabine resistance in cholangiocarcinoma accompanied by a reduction in P‐glycoprotein expression

Abstract: Increasing evidence revealed that ten‐eleven translocation 1 (TET1) plays an important role in tumorigenesis and chemoresistance, but its functions in gemcitabine resistance in cholangiocarcinoma (CCA) remain unknown. This study aims to investigate the effect of TET1 on gemcitabine resistance in CCA and the possible effect on P‐glycoprotein (P‐gp) expression encoded by multidrug resistance (MDR) genes. We established two kinds of gemcitabine‐resistant CCA cell lines and confirmed its specific features. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[ 22 ] As a result, SOCS1 dysfunction triggers MMP9 upregulation, which increases HCC cell growth, invasion, and metastasis. [ 22 ] A study from Wang et al [ 11 ] demonstrated that TET1 reverses gemcitabine resistance in cholangiocarcinoma (CCA), with overexpression of TET1 leading to increased sensitivity of CCA cells to gemcitabine. Furthermore, multivariate Cox regression analysis showed that TET1 expression was an independent risk factor ( P < .001) for the clinical results of CCA patients with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 22 ] As a result, SOCS1 dysfunction triggers MMP9 upregulation, which increases HCC cell growth, invasion, and metastasis. [ 22 ] A study from Wang et al [ 11 ] demonstrated that TET1 reverses gemcitabine resistance in cholangiocarcinoma (CCA), with overexpression of TET1 leading to increased sensitivity of CCA cells to gemcitabine. Furthermore, multivariate Cox regression analysis showed that TET1 expression was an independent risk factor ( P < .001) for the clinical results of CCA patients with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multivariate Cox regression analysis showed that TET1 expression was an independent risk factor ( P < .001) for the clinical results of CCA patients with chemotherapy. [ 11 ] In addition, Kaplan--Meier survival and the log-rank test showed that decreased expression of TET1 was associated with poorer prognosis of CCA patients with chemotherapy. [ 11 ] Thus, TET1 may be a promising target to overcome chemoresistance in CCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature regarding the use of gene therapy to chemosensitize CCA is scarce. Overexpression of ten-eleven translocation 1 (TET1), a methylcytosine dioxygenase that catalyzes DNA demethylation, enhances the sensitivity of CCA to gemcitabine, accompanied by a decrease in MDR1 expression [67]. In addition, overexpression of miR-199a-3p in the presence of cisplatin could decrease the proliferation rate and increase apoptosis of CCA cells, probably by regulating the expression of its target gene mTOR and reducing that of MRP1 [68].…”
Section: Strategies To Reduce Drug Effluxmentioning
confidence: 99%